Pengembangan Media Pembelajaran Interaktif Berbasis Discovery Learning Pada Mata Pelajaran Tata Hidang di Kelas XI SMK Pariwisata Mengwitani - Sri Indah Yani; Made Susi Lissia Andayani; Dessy Seri Wahyuni (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2022)
This study aims to produce discovery learning-based interactive learning media on tata hidang subjects in class XI of Mengwitani Tourism Vocational School and to find out the responses of teachers and students regarding the design of discovery learning-based interactive learning media on tata hidang subjects in class XI of Mengwitani Tourism Vocational School. This research is a research & development (R&D) type using the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation). The results of the calculation of the validity of content experts and media and design experts show that the validity level of 1.00 is included in the "Very High" validity level with the "Very Valid" criteria. The percentage result obtained from individual trials is 92% which includes the "Very Good" qualification. The results obtained from the small group trial were included in the "Good" qualification and the field trial included in the "Very Good" qualification. The results of the average student response obtained were 65.2 when converted into a response classification criteria table, indicating that it was included in the "Very Positive" category. The class average (x ) obtained from the teacher's response is 46, it is included in the "Very Positive" category. The Effectiveness Test obtained an N-Gain value of 0.84 so that the effectiveness test carried out showed that the interactive learning media product developed had a "High" effectiveness.